Effort Displayed During Appetitive Phase of Feeding Behavior Requires Infralimbic Cortex Activity and Histamine H1 Receptor Signaling - Riveros, María E.; Forray, María Ines; Torrealba, Fernando; Valdés, José L. (Frontiers in Neuroscience, 2019)
The chances to succeed in goal-directed behaviors, such as food or water-seeking, improve when the subject is in an increased arousal state. The appetitive phase of these motivated behaviors is characterized by high levels of behavioral and vegetative excitation. The key decision of engaging in those particular behaviors depends primarily on prefrontal cortical areas, such as the ventromedial prefrontal cortex. We propose that the infralimbic cortex (ILC) located in the medial prefrontal cortex induces an increase in arousal during the appetitive phase of motivated behavior, and that this increase in arousal is, in turn, mediated by the activation of the brain histaminergic system, resulting in higher motivation for getting food rewards. To test this hypothesis, we conduct a progressive ratio operant conditioning to test the degree of motivation for food, while simultaneously manipulating the histaminergic system through pharmacologic interventions. We found that the behavioral responses to obtain food in hungry rats were disrupted when the ILC was inhibited through muscimol infusion, blocking brain H1 histamine receptors by intracerebroventricular infusion of pyrilamine or by satiety. In contrast, the consummatory behavior was not affected by ILC inhibition. The extracellular histamine levels in the ILC were increased in direct correlation with the degree of motivation measured in the progressive ratio test. ILC inhibition also prevented this increase in histamine levels. The rise in extracellular histamine levels during the progressive ratio test was similar (ca. 200%) during the active or the resting period of the day. However, different basal levels are observed for these two periods. Our findings suggest that increased histamine levels during this behavior are not simply explained by the awaked state, but instead, there is a motivation-related release of histamine, suggestive of a specific form of brain activation. Serotonin (another critical component of the ascending arousal system) was also tested. Interestingly, changes in levels of this neuromodulator were not detected during the progressive ratio test. In conclusion, our results suggest that ILC activation and subsequent increase in brain histamine release are both necessary for the normal performance of a motivated behavior such as feeding.